Effects of supplementation of a basal diet of maize stover with different amounts of Leucaena diversifolia on intake, digestibility, nitrogen metabolism and rumen parameters in sheep - Hindrichsen, I.K.; Osuji, P.O.; Odenyo, A.A.; Madsen, J.; Hvelplund, T. (Elsevier, 2002)
The experiment was carried out using a replicated (3x3) Latin square design with six sheep, to assess, the effect of supplementing maize stover fed ad libitum at three levels (100, 150 or 200 g) of Leucaena diversifolia. The sheep had an initial live weight of 26.4 kg (+ or -) 1.78 kg. In each period feed intake, digestibility, nitrogen balance, microbial protein yield, rumen kinetics, passage rate and protozoa and total bacteria were measured. L. diversifolia contained 32.7 g N kg-1 dry matter (DM), while maize stover contained 4.4 g N kg -1 DM. There was a linear (P<0.05) increase in total DM intake, organic matter (OM) intake, neutral detergent fibre (NDF) intake, neutral detergent fibre nitrogen (NDF-N) intake and N intake. As level of supplement increased, faecal N increased linearly (P<0.001), leading to no effect on N retention. The apparent N digestibility of L. diversifolia was estimated to be as low as 22.1%. With increasing level of Leucaena supplementation, the supply of microbial nitrogen to the duodenum increased, both when measured with purine derivatives in urine (P<0.05) and when measured with purine in duodenum samples (P<0.05). Increasing level of Leucaena increased (P<0.05) total bacteria count in the rumen. L. diversifolia has limited value as a supplement to maize stover due to low protein digestibility.